Active photonic platforms for the mid-infrared to the THz regime using spintronic structures - Armelles Gaspar; Cebollada Alfonso (Nanophotonics, 2020)
Spintronics and Photonics constitute separately two disciplines of huge scientific and technological impact. Exploring their conceptual and practical overlap offers vast possibilities of research and a clear scope for the corresponding communities to merge and consider innovative ideas taking advantage of each other’s potentials. As an example, here we review the magnetic field modification of the optical response of photonic systems fabricated out of spintronic materials, or in which spintronic components are incorporated. This magnetic actuation is due to the Magneto Refractive Effect (MRE), which accounts for the change in the optical constants of a spintronic system due to the magnetic field induced modification of the electrical resistivity. Due to the direct implication of conduction electrons in this phenomenon, this change in the optical constants covers from the mid-infrared to the THz regime. After introducing the non-expert reader into the spintronic concepts relevant to this work, we then present the MRE exhibited by a variety of spintronic systems, and finally show the different applications of this property in the generation of active spintronic-photonic platforms.